The Protestant ethic and the spirit of capitalism - Weber, Max 1864-1920 (Alexander Street Press, 1958)
"THE PROTESTANT ETHIC AND THE SPIRIT OF CAPITALISM is considered a founding text in economic capitalism, economic sociology and sociology in general. In the book, Weber wrote that capitalism in Europe evolved when the Protestant ethic influenced large numbers of people to engage in work in the secular world, developing their own enterprises and engaging in trade and the accumulation of wealth for investment. In other words, the Protestant work ethic was a force behind a mass action that influenced the development of capitalism. This book is not a detailed study of Protestantism but rather an introduction into Weber's studies of interaction between moral ideas and economics. He argues convincingly about the American ethics and ideas that have so positively influenced the development of capitalistic financial prosperity, and thereby, both the personal and common good. Translated by leading sociologist Talcott Parsons, this was the first and still remains the seminal translation of Weber's main work." --Amazon website
Bibliographical references included in "Notes" (p. 185-284)
Erscheinungsjahr in Vorlageform:[1958]
Keywords: Evangelische Kirche; Geschichte 1905; Geschichte 1920; Capitalism / Religious aspects / Protestant churches; Protestant work ethic; Kapitalismus; Religion; Protestantismus; Theologische Ethik; Capitalism -- Religious aspects -- Protestant churches; Quelle